3He flux obtained from South Pole air and snow‐ice and its connection to interplanetary dust particles. (15th November 2021) - Farley, Kenneth A.; Taylor, Susan; Treffkorn, Jonathan; Lever, James H.; Gow, Anthony L.
Abstract: Researchers have characterized extraterrestrial (ET) helium, likely carried by interplanetary dust particles (IDPs), in deep‐sea sediments spanning more than the last 100 Myr. Here we complement those low resolution and deep time studies by measuring He in modern Antarctic air and recent ice. We analyzed 180 air filter samples collected in 2017 and 2018 at the South Pole and detected 3 He above blank levels in 178. The filters collected during the austral springs had elevated 3 He in multiple subsamples indicating the presence of many individual IDPs and potentially, a temporal variation in the ET small particle flux. Our calculated mean 3 He flux of 1.4 ± 1.2 × 10 −12 cc STP cm −2 ka −1 is the first such measurement from air samples. We also melted, filtered, and analyzed one hundred and forty‐one 1 m‐long ice sections from a ˜2000‐yr‐old South Pole core. We detected 3 He above blank levels in 139 of the 141 ice core samples and calculated an average flux of 1.2 ± 0.3 × 10 −12 cc STP cm −2 ka −1 . Our two flux values are within a factor of two of those calculated from stratospheric IDP concentrations, those previously measured for sections of the GISP2 and Vostok ice cores, and from sediment cores from different locations and ages. The similarity of these flux values over disparate time scales (1–10 8 yr) and geographic locations (90° S to equator) indicates modest temporal variability and remarkable agreement among diverse IDP archives. These data provide a compelling link from IDPs collected in the stratosphere to those recorded in deep time sedimentary archives.